Anti-IL-17A antibody-associated de novo vitiligo: Case report and review of literature - Su, Hsing-Jou; Chan, Yu-Pei; Shen, Peng-Chieh; Ku, Cheng-Lung; Ng, Chau Yee (Frontiers in Immunology, 2023)
Interleukin (IL)-17 inhibitor is a biological therapy approved for moderate-to-severe psoriasis and psoriatic arthritis. Common adverse event of IL-17 inhibitor includes injection site reaction, infections, nasopharyngitis, and headache. However, vitiligo associated with the use of IL-17 inhibitor was rarely reported in the previous literature. Here, we described a woman who developed de novo vitiligo after four months of IL-17A inhibitor treatment for psoriasis and psoriatic arthritis. Upon discontinuation of IL-17A inhibitor and shifting to a broader T cell inhibitor - cyclosporine, our patient had control of both psoriasis and vitiligo and achieved a 75% repigmentation after three months of oral cyclosporine without phototherapy. Due to the increasing use of anti-IL-17 biologics in psoriasis patients, clinicians should inquire about vitiligo's history before treatment and inform of the possible adverse effect.